Hsa_circ_0078767 Enhances Osteosarcoma Chemoresistance to Doxorubicin Through the Regulation of the miR-188-3p/GPX4 Axis - Tang Y; He Y; Wu L (Dove Medical Press, 2024)
Yin Tang,1- 5,* Yuzhe He,1- 4,* Lidong Wu1- 4 1Department of Orthopedic Surgery, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People's Republic of China; 2Orthopedics Research Institute of Zhejiang University, Hangzhou, Zhejiang, People's Republic of China; 3Key Laboratory of Motor System Disease Research and Precision Therapy of Zhejiang Province, Hangzhou, Zhejiang, People's Republic of China; 4Clinical Research Center of Motor System Disease of Zhejiang Province, Hangzhou, Zhejiang, People's Republic of China; 5Department of Orthopedic Surgery, Ningbo No.2 hospital, Ningbo, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Lidong Wu, Department of Orthopedic Surgery, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People's Republic of China, Tel +86-057187783777, Email wulidong777@sina.comBackground: Osteosarcoma (OS) is a primary malignancy of bone. The emergence of chemoresistance represents a persistent barrier to effective cancer patient care. This analysis sought to examine hsa_circ_0078767 as a mediator of doxorubicin (DOX) resistance in OS.Methods: Levels of hsa_circ_0078767, miR-188-3p, and glutathione peroxidase 4 (GPX4) in OS clinical tissue samples and cell lines were evaluated by quantitative polymerase chain reaction (qPCR) and Western blotting. Associations between hsa_circ_0078767 levels in clinical samples and patient overall survival were assessed with Kaplan-Meier curves. CCK-8 assays were utilized as a means of examining DOX half-inhibitory concentration (IC50) values. RNA immunoprecipitation and pull-down, as well as reporter assays, investigated interactions between hsa_circ_0078767, miR-188-3p, and GPX4 within OS cells exhibiting DOX resistance.Results: OS patient tissues and cell lines resistant to DOX exhibited elevated hsa_circ_0078767 and GPX4 expression together with a reduction in miR-188-3p levels. Inhibiting hsa_circ_0078767 expression contributed to a profound decrease in the ability of OS tumors to resist DOX. Mechanistically, it was determined that hsa_circ_0078767 can enhance DOX chemoresistance through its ability to bind and sequester miR-188-3p, which otherwise negatively modulates GPX4 to enhance chemosensitivity. Accordingly, the sequestration of miR-188-3p by hsa_circ_0078767 led to the derepression and upregulation of GPX4.Conclusion: Hsa_circ_0078767 was found to modulate miR-188-3p/GPX4 signaling to enhance OS cell resistance to DOX treatment and facilitate disease progression. As such, hsa_circ_0078767 may represent a valuable biomarker or target for use in the context of OS patient management.Keywords: GPX4, hsa_circ_0078767, doxorubicin, miR-188-3p, osteosarcoma